A Historical Study Of The Development Of Islamic Law In The Nusantara - Nabil Amir, Ahmad; Abdul Rahman, Tasnim (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This paper examines the role and function of Islam in shaping the judicial orientation of Malaysia, tracing the influence and evolution of Islamic law within the national legal framework from the Malay Sultanate era through colonial and post‐independence periods. It begins by recounting the formation of Malay political entities and the transfer of sovereignty from Islamic rulers to Portuguese, Dutch, Japanese, and British colonial powers. During these transitions, Islamic belief systems and legal traditions faced challenges from Orientalist thought, Westernization, and modernization—forces that undermined Islamic moral values and Malay identity. These pressures were exacerbated by the fall of the Ottoman Empire, the last caliphate, which had served as a unifying banner for Muslims across the region. Employing qualitative analysis based on library research and literature review, the study finds that colonial interventions—driven by secular, nationalist, and communist ideologies for political gain—impeded the enforcement of shariah. Moreover, secular indoctrination during and after colonial rule dominated the intellectual and cultural landscapes of Muslim societies.